Penetapan Kadar Senyawa Saponin Pada Batang dan Daun Beberapa Tanaman Pada Family Asteraceae - Ismi Rahayu Eka Pratiwi; Zainal Abidin; Aminah Aminah (PHARMACY UMI JOURNAL SYSTEM, 2023)
The plants of Asteraceae family have secondary metabolite compounds, namely flavonoids, saponins, tannins, essential oils, polyphenols, and terpenoids. The research aimed to compare saponin content on stems and leaves of Asteraceae family plants using gravimetry methods. Besides, it compares saponin content using colorimetry methods based on different solvents. The research used literature review methods. The data search was done through the database using a search engine such as Google Scholar and PubMed. By gravimetry method, Vernonia amygdalina plant contained the highest saponin content of 7.92±0.46% on the leaf; on the stem, Helianthus Annuus L. plant carried the highest saponin content of 7.74±2.80%. Meanwhile, by colorimetry method, the ethyl acetate extract of Hypochaeris radicata L. plant contained the highest saponin on the leaf showing the rate of 16. 67±0.01 mg DE/100 g.